2007
DOI: 10.1638/2006-0027r.1
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Associated With a Pneumonic Epizootic in Rocky Mountain Bighorn Sheep (Ovis Canadensis Canadensis)

Abstract: A comprehensive study of a pneumonic epizootic was initiated when the first signs of disease were noted in a metapopulation of bighorn sheep inhabiting Hells Canyon, bordering Idaho, Oregon, and Washington. A total of 92 bighorn sheep were tested for etiologic agents during the following 6-mo study period. The study population included bighorn sheep believed to be the subpopulation in which disease was first noted, and these sheep were translocated to a holding facility in an effort to contain the disease (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 18 publications
1
58
0
1
Order By: Relevance
“…5). We chose to determine PI-3-neutralizing titers because several BHS herds have been reported to test positively for anti-PI-3 Abs (26,29). Results from the virus neutralization assays revealed that the BHS serum and colostrum samples had high levels of PI-3-neutralizing Abs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). We chose to determine PI-3-neutralizing titers because several BHS herds have been reported to test positively for anti-PI-3 Abs (26,29). Results from the virus neutralization assays revealed that the BHS serum and colostrum samples had high levels of PI-3-neutralizing Abs.…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of bronchopneumonia in previously healthy populations of BHS often result in high death rates among all age groups initially, followed by years of impaired recruitment due to pneumonia in lambs (5,21,24,28). During these outbreaks, members of the genera Mannheimia, Bibersteinia, and Pasteurella, including Mannheimia (Pasteurella) haemolytica, Bibersteinia (Pasteurella) trehalosi, and Pasteurella multocida, have commonly been isolated from pneumonic lungs (16,26). Of these, M. haemolytica has consistently been shown to cause fatal bronchopneumonia in BHS under experimental conditions (9,12,20).…”
mentioning
confidence: 99%
“…Bibersteinia trehalosi causes septicemia in lambs and pneumonia in cattle, domestic sheep, and bighorn sheep in North America 8,18,22,26 but, to our knowledge, has not been reported as a cause of botryomycosis. The purpose of this report is to describe a case of subcutaneous botryomycosis caused by B. trehalosi in a Texas Longhorn steer.…”
mentioning
confidence: 80%
“…They may act alone or in concert with other agents associated with pneumonia in bighorn sheep (Miller, 2001;Rudolph et al, 2003Rudolph et al, , 2007. Mycoplasma ovipneumoniae infections have been associated with chronic respiratory infections, poor growth, and exercise intolerance of lambs in domestic sheep herds (Sullivan et al, 1973;Timoney et al, 1988) and have been suggested as a possible cause of population-limiting pneumonia in bighorn sheep adults and lambs (Besser et al, 2008).…”
mentioning
confidence: 99%
“…All cultures, with one exception, were PCR positive for M. arginini, and no animal was culture negative and PCR positive for M. arginini. Although M. arginini and M. ovipneumoniae are most frequently detected in bighorn sheep (Rudolph et al, 2007;Besser et al, 2008), the genus primers used in this study allow for the detection of additional species. Cultures of any Mycoplasma species also would be useful in strain typing and virulence factor studies.…”
mentioning
confidence: 99%